Conventional biotyping revealed Mycoplasma and antimicrobial resistant Escherichia coli and Salmonella isolates during disease outbreak in broiler farms and hatcheries in Leyte, Philippines - Lañada, Eugene B.; Portugaliza, Harvie P.; Blanza, Analyn I.; Espejo, Mercy Cheryll C.; Pagente, Ma. Delia A. (Annals of Tropical Research, 2022)
A respiratory disease outbreak investigation was carried out from October to December 2015 in three broiler farms and two hatcheries in Leyte. Three- to seven-day-old chicks from farms were initially brought to CVM diagnostic laboratory for necropsy and microbial analyses. Subsequent visits to hatcheries and farms were made for random swabbing and sampling of physical facilities, equipment, vehicle, unhatched eggs, 18-day old eggs, eggshells, and day-old chicks. Chick necropsy, embryo examination, and bacteriological method for Escherichia coli, Salmonella, and Aspergillus were performed. Antimicrobial sensitivity testing was conducted for Salmonella and E. coli isolates. The main clinical sign observed in chicks was dyspnea. Necropsy revealed consistent bilateral fibrinous airsacculitis and perihepatitis with few cases of pericarditis, wherein sampled organs consistently showed the presence of E. coli. Out of 83 samples collected, 19 (22.89%) Salmonella, 40 (48.19%) E. coli, and no Aspergillus were isolated. Most E. coli were isolated from chick embryos and necropsied chickens, while Salmonella isolates were mostly from the environment. Mycoplasma was isolated from 63.64% (7/11) of sampled lungs, air sacs, and liver from unhatched embryos (100%), 18-day old embryos (50%), and day-old chicks (33.33%). The majority of Salmonella and E. coli isolates showed multidrug resistance against amoxicillin, chloramphenicol, erythromycin, trimethoprim/sulfamethoxazole (TMPS), and tetracycline. Few isolates were sensitive to ciprofloxacin. Our results should raise awareness on the occurrence of antimicrobial-resistant E. coli and Salmonella, and coinfection with Mycoplasma among broilers in Leyte. Therefore, proper selection and usage of antibiotics should be advocated in all poultry farms.